Cutaneous leiomyoma of scalp: a rare case report with review of literature - Fatima, Qadir; Singh, Omprakash; Kothari, Dharm Chand; Godara, Susheela Kumari (International Journal of Research in Medical Sciences, 2017)
Skin is the largest organ of the body and many types of tumor arises from different part of skin layer. A leiomyoma is an uncommon, benign tumour of smooth muscle of skin derived from the arrector pili muscle of skin. These lesions can develop wherever smooth muscle is present, but malignant transformation probably does not occur. Cutaneous leiomyomas or piloleiomyomas appear as small (0.5-2 cm) firm skin coloured nodules. They arise from the arrector pili muscles which are responsible for making your hairs stand on end. Multiple lesions may develop, often in clusters and commonly in a segmental distribution. These nodules are benign, so are only of concern because of their appearance or their tendency to be tender if knocked. Female patients with cutaneous leiomyomas may also develop uterine leiomyomas (fibroids), and very rarely leiomyomas can be associated with renal cell carcinoma (hereditary leiomyomatosis and renal cell cancer). We report a case cutaneous leiomyoma of scalp in a 22 year old male who present with the complaints of scalp swelling.